2017
DOI: 10.3102/0162373717714056
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teacher Match on Students’ Academic Perceptions and Attitudes

Abstract: Using student survey data from six U.S. school districts, we estimate how assignment to a demographically similar teacher affects student reports of personal effort, happiness in class, feeling cared for and motivated by their teacher, the quality of student-teacher communication, and college aspirations. Relying on a classroom fixed-effects strategy, we show that students assigned to a teacher with similar demographic characteristics experience positive benefits in terms of these academic perceptions and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(109 citation statements)
references
References 78 publications
(133 reference statements)
2
99
0
Order By: Relevance
“…Teacher–child match is also related to positive student reports of their teachers. Results from a secondary analysis of the MET study found that children assigned to racially/ethnically matched teachers reported greater positive perceptions and attitudes about their happiness in class, and feelings of being cared for and motivated by their teacher (Egalite & Kisida, ). These studies suggest teacher and child race/ethnicity may matter in the classroom by influencing how teachers perceive children and vice versa (Egalite & Kisida, ); and that racial/ethnic alignment between children and their teachers may provide culturally relevant role models for children and engender warmer learning environments (Blake et al., ; Cherng & Halpin, ).…”
Section: Theoretical Framework: Cultural Synchrony Hypothesismentioning
confidence: 99%
“…Teacher–child match is also related to positive student reports of their teachers. Results from a secondary analysis of the MET study found that children assigned to racially/ethnically matched teachers reported greater positive perceptions and attitudes about their happiness in class, and feelings of being cared for and motivated by their teacher (Egalite & Kisida, ). These studies suggest teacher and child race/ethnicity may matter in the classroom by influencing how teachers perceive children and vice versa (Egalite & Kisida, ); and that racial/ethnic alignment between children and their teachers may provide culturally relevant role models for children and engender warmer learning environments (Blake et al., ; Cherng & Halpin, ).…”
Section: Theoretical Framework: Cultural Synchrony Hypothesismentioning
confidence: 99%
“…For example, there are considerably more women faculty in the life sciences as compared with the physical sciences or engineering (National Academy of Sciences, 2007). At the same time, research shows that, when instructors and students are aligned according to a variety of demographic characteristics such as gender and race, it improves student outcomes (Dee, 2004) and experiences (Egalite and Kisida, 2018). When students have instructors who are more "like them," this provides them with instructors who can more easily serve a role models and who also are more likely to understand the particular racialized or gendered experiences of the students.…”
Section: Demographic Variation (People)mentioning
confidence: 99%
“…The mismatch between the races of teachers and their students has real consequences for students, as numerous studies have found consistent benefits of racial congruence, including fewer absences and suspensions, lower dropout rates, higher academic achievement, and a higher probability of placement in gifted programming (Goldhaber and Hansen, 2010;Grissom and Redding, 2016;Joshi, Doan, and Springer, 2018). Racial match between teachers and students also leads to positive student perceptions of teachers (Egalite and Kisida, 2017) and significant long-term gains in educational attainment (Gershenson et al, 2017).…”
Section: Key Findingsmentioning
confidence: 99%